Evaluation of the Cytotoxicity of Aqueous Extract and Oleo-Essential Oil of Dorema ammoniacum Plant Oleo-Gum Resin in Some Human Cancer Cell Lines - Pardis Mohammadi Pour; Spideh Bidad; Gholamreza Bahrami; Leila Hosseinzadeh; Mahdi Mojarrab; Mohammad Hosein Farzaei (Analytical Cellular Pathology)
Background and Aim. This study is aimed at examining the cytotoxic and apoptotic activity of the aqueous extract and essential oil of Dorema ammoniacum D. Don gum toward some cancer cell lines. Experimental Procedure. The aqueous extract of D. ammoniacum oleo-gum resin was obtained by decoction method, and essential oil was prepared using distillation method by Clevenger apparatus. The cytotoxic activity of aqueous extract and essential oil of D. ammoniacum oleo-gum resin toward A549, PC3, HeLa, and MCF7 cell lines was examined by MTT method. Following selecting the most potent extract and essential oil, the mechanism of activity of these samples was examined by determining caspase-3 and caspase-9 activity, mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) enzymatic activity. Results. Aqueous extract and essential oil reduced the viability of A549 cancer cells in a concentration-dependent manner. The lowest inhibitory concentrations (IC50) for both samples of D. ammoniacum oleo-gum resin were 10 and 2.5 μg/ml for 24 hours in A549 cell line, respectively. After treatment with extract and essential oil of D. ammoniacum oleo-gum resin, ROS increased significantly compared to the control group. Although changes in caspase-3 did not show a significant increase in extract, the caspase-3 was found to be increased after exposure to essential oil and caspase-9 was downregulated after exposure to essential oil. Also, exposure to essential oil of D. ammoniacum caused a reduction in MMP level. Conclusion. Based on results, the cytotoxic effect of essential oil of D. ammoniacum can induce apoptosis toward A549 cell line via induction of oxidative stress, MMP depletion, and caspase-3 activation, which is independent to mitochondrial cytochrome c release and caspase-9 function.